The role of P-selectin/PSGL-1 in regulating NETs as a novel mechanism in cerebral ischemic injury - Li, Xiao; Ma, Yamin; Wang, Dongbin (Frontiers in Neurology, 2024)
In recent years, substantial advancements have been made in understanding the pathophysiology of ischemic stroke. Despite these developments, therapeutic options for cerebral ischemia remain limited due to stringent time windows and various contraindications. Consequently, there has been a concentrated effort to elucidate the underlying mechanisms of cerebral ischemic injury. Emerging research indicates that neutrophil extracellular traps (NETs) exacerbate inflammation and damage in ischemic brain tissue, contributing to neuronal cell death. The inhibition of NETs has shown potential in preventing thrombosis and the infiltration of immune cells. Central to the formation of NETs are P-selectin and its ligand, P-selectin glycoprotein ligand-1 (PSGL-1), which represent promising therapeutic targets. This review explores the detrimental impact of P-selectin, PSGL-1, and NETs on cerebral ischemia. Additionally, it delineates the processes by which P-selectin and PSGL-1 stimulate NETs production and provides evidence that blocking these molecules reduces NETs formation. This novel insight highlights a potential therapeutic avenue that warrants further investigation by researchers in the field.